2001
DOI: 10.1016/s0014-5793(01)02652-7
|View full text |Cite
|
Sign up to set email alerts
|

Down modulation of IL‐18 expression by human papillomavirus type 16 E6 oncogene via binding to IL‐18

Abstract: To understand modulation of a novel immune-related cytokine, interleukin-18, by human papillomavirus type (HPV) 16 oncogenes, HaCaT, normal keratinocyte cell line, and C-33A, HPV-negative cervical cancer cell line, were prepared to establish stable cell lines expressing E6, E6 mutant (E6m), E6E7, or E7 constitutively. Expressions of various HPV oncogene transcripts were identified by RT-PCR. Expression of HPV oncogene E6 was reversely correlated to the expression of interleukin-18, a novel pro-inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 50 publications
4
59
0
4
Order By: Relevance
“…An E6 oncoprotein-mediated reduction in expressed interleukin-8 (IL-18) CD8 + was also observed [60].…”
Section: Humoral Immune Responses and Cell-mediated Immune Responses mentioning
confidence: 96%
See 4 more Smart Citations
“…An E6 oncoprotein-mediated reduction in expressed interleukin-8 (IL-18) CD8 + was also observed [60].…”
Section: Humoral Immune Responses and Cell-mediated Immune Responses mentioning
confidence: 96%
“…The lipid core peptide (LCP), a vaccine delivery system incorporating lipoamino acids, was used to produce vaccine candidates against HPV-16 [104]. Moyle et al demonstrated that an LCP system that incorporated the long sequence E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] (known as 8Q) with CTL, T helper cell, and B cell epitopes was self-adjuvanting and reduced tumor size. This epitope was unable to prevent TC-1 tumors when delivered alone [104].…”
Section: Vaccine Deliverymentioning
confidence: 99%
See 3 more Smart Citations